Pelaksanaan pengajaran dan pembelajaran sejarah sekolah-sekolah di Malaysia 1957-1989 / Sharipah Aini Jaafar - Sharipah Aini , Jaafar (2018)
This research discusses on the implementation of teaching and learning History in Malaysian schools from 1957 to 1989. The implementation of this research is due to the fact that individual identity and love for the country among Malaysian citizens are not up to par. This is followed by the unsatisfactory results of the SPM examination nationwide. Therefore, the objective of this research is to study how far the implementation of History is foundation-wise. Apart from that, it also covers the syllabus and the teaching and learning methods of History during that specific time period. Furthermore, it is to identify and analyze the setbacks connected to challenges and obstacles in the implementation of teaching and learning History. The objective of this research broadens its area to unfolding the steps and strategies in dealing with setbacks in teaching and learning History in Malaysian schools from 1957 to 1989. This research is a qualitative research which touches on library research and open individual interviews. Library research is done to study and analyze primary sources such as files, official records, and personal letters apart from secondary sources such as books, newspapers, and magazines. The scope of this research starts in 1957 after Malaysia gained its independence and took its first step in shaping its own leadership style. This research ends in 1989 after History became a core subject. The research findings show that a number of policies for History have been made to improve individual identity and unity among races. It is noted that there were several challenges and obstacles during the implementation of History in schools. These include the learning system which is solely examination-based, insufficient circulation of textbooks, flaws in the content and accuracy of facts in textbooks, and also the teaching method of History which is teacher-oriented. With all being said, numerous steps and strategies have been taken by the Ministry and NGOs such as detection and evaluation strategies, Student Integration Plan for Unity (RIMUP) programme, reevaluation of curriculum and textbooks, plus the co-operation between Malaysian vi Historical Society and the Ministry of Education (MOE) in dealing with the setbacks faced until this subject is recognized as a core subject in 1989.